Pembuatan Alat Pencacah Rumput dan Pengering Kotoran untuk Meningkatkan Produktivitas Sapi Perah di Kelurahan Mulyorejo - Luthfi Indana; Rosyida Fajri Rinanti; Viry Puspaning Ramadhan; Indra Dwi Laksana; Moch. Rizky Putra Hidayatullah (Jurnal Pemberdayaan Masyarakat, 2024)
Dairy farmers from the Mulyo Farmers group, located in Mulyorejo Village, Sukun District, Malang City, are experiencing problems with feed productivity because dairy cows require fresh grass for their consumption. The cow dung on this farm has not been utilized properly, resulting in waste that can pollute the river flow in the surrounding environment. The purpose of this service is to provide solutions to these issues. The methods used in this service include socialization about the dangers of cow dung waste and its utilization, training in creating milk packaging with market value, and developing tools for shredding and drying cow dung. The results of this service activity indicate that farmers can save time and money on feed purchases by up to 30% because the grass can be chopped and consumed by all the cows. Additionally, cow dung can be dried and sold, increasing the income of the Farmers Group. Public knowledge about the dangers of cow dung and its utilization increased from level 2 to level 6, while awareness of dairy product packaging improved from 10% to 40%.